Mapping the landscape of techno-pedagogical research - Wawan Setiawardani; Rudi Susilana; Rusman Rusman (Himpunan Pengembang Kurikulum Indonesia, 2026)
The rapid development of global technology has significantly changed various aspects of education, transforming traditional pedagogical practices to accommodate new methodologies. Despite the crucial role of technopedagogy in improving education systems, including curriculum development, teacher knowledge, and learning outcomes, significant gaps remain in understanding its evolving impact on educational transformation. This study examines research trends in technopedagogy over the past decade to identify emerging topics in this field. Using a bibliometric research design, data were collected from the Scopus database, utilizing keywords such as “technopedagogy,” “technology pedagogy,” “teaching,” and “learning.” The collection process followed the SALSA (Search, Assessment, Synthesis, and Analysis) framework, resulting in a comprehensive dataset of 1,744 documents. Bibliometric analysis conducted in R revealed a consistent increase in publication volume and citation rates each year, with a significant spike in 2018. The results further indicate that the United Kingdom and the United States are leading countries in technopedagogy research. Key thematic trends identified include hybrid learning, educational challenges, the impact of COVID-19, and online teaching practices. This research emphasizes the importance of continued exploration of these trends to understand the implications of technopedagogy in educational contexts fully. Abstrak Pesatnya perkembangan teknologi global telah mengubah berbagai aspek pendidikan secara signifikan, mentransformasi praktik pedagogi tradisional untuk mengakomodasi metodologi baru. Meskipun teknopedagogi berperan krusial dalam meningkatkan sistem pendidikan, termasuk pengembangan kurikulum, pengetahuan guru, dan hasil belajar, masih terdapat kesenjangan yang signifikan dalam memahami dampaknya yang terus berkembang terhadap transformasi pendidikan. Studi ini mengeksplorasi tren penelitian di bidang teknopedagogi selama dekade terakhir, dengan tujuan mengidentifikasi topik-topik yang muncul dalam bidang ini. Menggunakan desain penelitian bibliometrik, data dikumpulkan dari basis data Scopus, menggunakan kata kunci seperti